Collaborative Inventory Management in Chinese Hospital Supply Chain: Barriers and Implementation - Wang, Yingfei (2012)
With the development of supply chain, the collaborative supply chain management has increasing popular worldwide in recent years. There are many advanced method of achieving supply chain collaboration, such as VMI and CPFR, which focus on inventory management. In addition, it has been adopted by many industries such as manufacture (Dell) and retail (Wal-Mart).